Non-glycemic Adverse Effects of Insulin - Guarneri, Alissa M.; Hoffman, Robert P. (Current Diabetes Reviews, 2022)
Insulin is primarily considered for its glycemic effects in patients with diabetes. There are, however, non-glycemic adverse effects of insulin that may significantly impact patient health and interfere with glycemic control. Insulinogenic edema primarily occurs with rapid improvement in glycemic control either in patients with newly discovered diabetes or in patients with poorly-controlled diabetes. Insulin-induced sympathetic activation, vasodilation, changes in vascular permeability, and most importantly, sodium retention play significant etiologic roles in the development of edema. Clinically, it is usually self-limited, but significant complications can develop. Allergic reactions to all insulin preparations and various compounds used in insulin formulations with a wide range of severity have been reported. Frequently, changing the type of insulin or delivery method is sufficient, but more advanced treatments such as insulin desensitization and anti-IgE antibody treatment may be needed. Lipohypertrophy and lipoatrophy frequently develop with the overuse of injection sites. Lipohypertrophy can affect tissue insulin absorption and glycemic control.
Keywords: lipoatrophy